2005
DOI: 10.1089/ham.2005.6.327
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude and the Eye: A Case Controlled Study in Clinical Ocular Anthropometry of Changes in the Eye

Abstract: Tribal natives of two spatially separate districts of Lahaul-Spiti (mean altitude = 3300 m) and Kinnaur (mean altitude = 1,700 m) in the Himalayan state of Himachal Pradesh have lived for centuries as closed isolated groups, marrying within the local community up to the recent past. Studies on highland natives in the Andes have shown differences in chest diameters, lung volumes, hematocrit, and the like, in those living at high altitudes. We wanted to study whether stay at high altitude for generations confers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…It is known that living at altitudes above 3000 m has biological effects on humans [ 4 , 5 ]. The unique plateau environment comprises low air pressure, reduced oxygen, dryness, cold weather, sunshine and exposure time, intense solar infrared light, intense ultra-violet radiation, and long winters, which all have effects on the human body, in general, and on the eyes in particular [ 6 , 7 ]. Because Tibet is located on the high-altitude Qinghai-Tibet plateau, the environment could be expected to affect the ocular health of people living there, but not much is known about the rates of eye diseases in the plateau region.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that living at altitudes above 3000 m has biological effects on humans [ 4 , 5 ]. The unique plateau environment comprises low air pressure, reduced oxygen, dryness, cold weather, sunshine and exposure time, intense solar infrared light, intense ultra-violet radiation, and long winters, which all have effects on the human body, in general, and on the eyes in particular [ 6 , 7 ]. Because Tibet is located on the high-altitude Qinghai-Tibet plateau, the environment could be expected to affect the ocular health of people living there, but not much is known about the rates of eye diseases in the plateau region.…”
Section: Discussionmentioning
confidence: 99%
“…The mean intercanthal index in the Chakma females indicated that their eyes were intermediate. Bali et al [33] reported that the individuals who are living at a high altitude has significantly wider intercanthal width and biocular width, thus larger intercanthal index. As the study populations of the present study live in high altitude, they show larger intercanthal index.…”
Section: Discussionmentioning
confidence: 99%
“…Other distinguishing features of Tibetan include a relative lower education level than China inland, lower population mobility and easy to follow up. The differences of regional environment and economics are reported to have influence on human body development and disease composition [8]. Whether the above unique differences affect pediatric eye diseases is not known until recently.…”
Section: Introductionmentioning
confidence: 99%